2016
DOI: 10.1002/bip.22852
|View full text |Cite
|
Sign up to set email alerts
|

Conformational preferences and synthesis of isomers Z and E of oxazole‐dehydrophenylalanine

Abstract: Dehydrophenylalanine, ΔPhe, is the most commonly studied α,β-dehydroamino acid. In nature, further modifications of the α,β-dehydroamino acids were found, for example, replacement of the C-terminal amide group by oxazole ring. The conformational properties of oxazole-dehydrophenylalanine residue (ΔPhe-Ozl), both isomers Z and E, were investigated. To determine all possible conformations, theoretical calculations were performed using Ac-(Z/E)-ΔPhe-Ozl(4-Me) model compounds at M06-2X/6-31++G(d,p) level of theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…To complete the preparation of β-chlorodehydroalanine model structures, the isomerization from the isomers Z into E assisted by UV irradiation was performed. The photoisomerization Z / E of simple dehydroamino acid residues is known. , However, according to the best of our knowledge, the application of this reaction to the β-halogenodehydroalanyl residue is reported for the first time here. The optimal reaction conditions in this case include the irradiation of the reaction mixture with UV light with a maximum wavelength of 366 nm at 5 h with an intensity of 400–440 μW/cm 2 (Figure d).…”
Section: Resultsmentioning
confidence: 94%
“…To complete the preparation of β-chlorodehydroalanine model structures, the isomerization from the isomers Z into E assisted by UV irradiation was performed. The photoisomerization Z / E of simple dehydroamino acid residues is known. , However, according to the best of our knowledge, the application of this reaction to the β-halogenodehydroalanyl residue is reported for the first time here. The optimal reaction conditions in this case include the irradiation of the reaction mixture with UV light with a maximum wavelength of 366 nm at 5 h with an intensity of 400–440 μW/cm 2 (Figure d).…”
Section: Resultsmentioning
confidence: 94%
“…In our previous studies, we have analysed the conformational properties of oxazole–amino acid for analogous residues (Siodłak et al 2014a ; Staś et al 2016b ). Comparison of the relative energy of oxazole– and thiazole–amino acid conformers with the same side chain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that modifications of peptide main chain or side chain as N -methylation (Siodłak et al 2006 , 2008 , 2012 ; Broda et al 2005 , 2009 ), C -terminal ester bond (Siodłak et al 2010 , 2011 ; Siodłak and Janicki 2010 ), dehydration of side chain (Buczek et al 2014 ), cyclization (Staś et al 2016a ), and many more (Jwad et al 2020 ; Gil et al 2009 ; Paranthaman 2018 ) have a considerable influence on preferred conformation. This includes the introduction of a five-membered heterocycle, such as oxazole (Siodłak et al 2014a ; Staś et al 2016a , b ) or thiazole, into a peptide main chain as an isosteric replacement of amide group. Peptides that contain heterocyclic amide isosteres are usually more rigid than the corresponding homodetic cyclic peptide (Jwad et al 2020 ; Abbenante et al 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Azole rings can be also used as trans replacement agents (Kaczmarek et al 2021;Lenartowicz et al 2022). Our previous studies show that the amino acid residues containing azole rings in the main chain possess unusual conformational properties (Siodłak et al 2014b;Staś et al 2026aStaś et al , 2016bStaś et al , 2021. Thiazole and oxazole amino acids tend to adopt the unique semi-extended conformation β2 (φ, ψ ≈ 180°, 0°), especially in weakly polar environments, where this global conformation is stabilized through the formation of the internal N-H•••N hydrogen bond, atypical for standard residues.…”
Section: Introductionmentioning
confidence: 99%